Three-dimensional finite element modeling of pacinian corpuscle - Yelke, Serkan. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2008., 2008)
Understanding the mechanics of Pacinian corpuscle (PC) is a fundamental necessity in order to contribute to tactile sense studies. It is proposed that the geometry of PC may have impact on its mechanics. A three-dimensional ovoid shape PC model was developed using the finite element method. The viscoelastic coefficients were included to involve time dependent material properties and to observe whether the band-pass filtering characteristics of PC obtained from neurophysiological data may be observed in the finite element model of PC or not. Static and dynamic stimulations were given to the model as inputs to mimic experiments. Data from both model and experiments were compared and it was concluded that geometry has no determining effect on the mechanics of PC. Besides, viscoelastic property, alone, was not enough to comprehend the underlying reason of band-pass filtering characteristics of PC. Homogeneous structure may not be the only answer to the mismatch of the results since the filtering property was not observed in experimental studies. If the homogeneous structure of the model is developed to a multilayered structure, more reliable results would have been obtained which needs to be tested in new studies.|Keywords: Pacinian corpuscle, finite element method, viscoelasticity, band-pass filter, mechanoreceptor.
Keywords: Pacinian bodies.; Finite element method.; Viscoelasticity.; Mechanoreceptors.